2015
DOI: 10.1016/j.ijimpeng.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of relative density on the crushing and energy absorption of open-cell foams under impact

Abstract: a b s t r a c tMicromechanically accurate random foams are used to examine the effect of relative density on the crushing response and energy absorption of aluminum open-cell foams for a range of loading rates. Random soap froth microstructures generated with the Surface Evolver software are dressed with shear deformable beam elements with material distribution that mimics measured values. Foam models of relative densities between 3.67% and 10.0% are crushed first quasi-statically and then dynamically in a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Recently, experiments on dynamic crushing of aluminium foam (Barnes et al, 2014) and 3D simulations of the compaction of closed metal foam (Zheng et al, 2014) confirmed the validity of the proposed above approach, which is based on the characteristic Hugoniot curves. A more recent study based on the micro-structural analysis of the dynamic uniaxial response of open cell aluminium foam (Gaitanaros and Kyriakides, 2015) confirmed the parabolic character of the Hugoniot strain-velocity dependences used for various material densities. The major advantage of the theoretical methodology based on the Hugoniot strain-velocity relationship is that it allows analysing the primary and reflected waves thus increasing the accuracy of the energy absorption predictions under impact and blast.…”
Section: Theoretical Modelsmentioning
confidence: 70%
“…Recently, experiments on dynamic crushing of aluminium foam (Barnes et al, 2014) and 3D simulations of the compaction of closed metal foam (Zheng et al, 2014) confirmed the validity of the proposed above approach, which is based on the characteristic Hugoniot curves. A more recent study based on the micro-structural analysis of the dynamic uniaxial response of open cell aluminium foam (Gaitanaros and Kyriakides, 2015) confirmed the parabolic character of the Hugoniot strain-velocity dependences used for various material densities. The major advantage of the theoretical methodology based on the Hugoniot strain-velocity relationship is that it allows analysing the primary and reflected waves thus increasing the accuracy of the energy absorption predictions under impact and blast.…”
Section: Theoretical Modelsmentioning
confidence: 70%
“…On the other hand, the micromechanical approach considers the microstructure of a real cellular solid. The micro-mechanical models have evolved from simple models with idealised cell geometries and microstructures; such as Kelvin cell models; to more sophisticated random models obtained using the Surface Evolver software [179]. The micromechanical models of foam material can overcome the limitations reported for macromechanical models and can provide more accurate predictions for the crushing behaviour of such materials.…”
Section: Dynamic Behaviour Of Foam Materialsmentioning
confidence: 99%
“…Thanks to their remarkable energy absorption [3][4][5] and vibration damping [6], metallic porous materials can be applied in the automotive industry. Hence over the years, people have paid much attention to the thermal properties [1,[7][8][9][10][11][12] and the mechanical properties [4,5,[13][14][15][16][17][18] of porous materials. Catalyst carrier [19], high-temperature applications [20,21], sandwich panels [22] and porous electrode for fuel cell [19] are also typical examples of porous material applications.…”
Section: Introductionmentioning
confidence: 99%